Il melodramma e i suoi libretti: un educatore dell'immaginario tra borghesia e popolo (II parte) - Franco Cambi (Firenze University Press, 2011)
This article contains the arguments already addressed by the author in the previous issue of the magazine. In this essay he explores the figure of Wagner and ana- lyzes his work and his personality: musical genius, art theoretician and teacher of thinking. There are many other great authors and topics addressed in theessay, Adorno, Gramsci, etc. and the essay concludes with a reflection on the subject 'courtly' and 'embourgeoisement' of tragedy.